Augmented Reality Needs Analysis in Science Learning: Teacher's Perspective - Rivan Gestiardi; Fulusia Nurmawati; Idam Ragil Widianto Atmojo (AL-ISHLAH: Jurnal Pendidikan, 2022)
The use of Augmented Reality can increase the activities of students to blend into a natural learning environment no longer abstract. It was merging virtual objects and fundamental interactions anytime and anywhere, which can present 3D objects, which are the most important features of Augmented Reality, resulting in a learning experience different from before. The main purpose of this study is to focus on teachers' views related to material needs and the supporting factors in the acceptance of Augmented Reality, especially in science learning in elementary schools. This study took a sample of teachers in 20 public elementary schools in Surakarta, Central Java, Indonesia, with a total population of 200 teachers with a sample of 30 teachers. The sample includes teachers who have years of teaching experience with different schools. The result is that STEM and Augmented Reality have not been maximally applied in schools; There needs to be broader socialization and training to the need for various Augmented Reality-based science materials that need to be developed.